PENINGKATAN HASIL BELAJAR MELALUI PRAKTIKUM MENGGUNAKAN MODEL INKUIRI TERBIMBING DENGAN PENDEKATAN TARL - Aini, Qurrotul; Budiyanto, Moh.; Anwar, Anita Rosana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the improvement in student learning outcomes through practicum using the Inquiry model with the TaRL approach. The low learning outcomes are caused by teachers only emphasizing theory in learning without having to involve students in direct practice so that it can make students bored and not enthusiastic about participating in learning. This research used a type of classroom research (PTK) and was carried out at SMPN 5 Pamekasan with samples used in class VIII-A, totaling 30 students, carried out in 3 cycles. The instruments used are the results of observations and learning evaluation tests using classical completeness. Based on the results of research data that was carried out, cycle I was 77%, cycle II was 80%, while cycle III was 90%. This research proves that applying the Inkuri model through practicum with Tarl can improve learning outcomes.